Metabolic characteristics of Africans with normal glucose tolerance and elevated 1-hour glucose: insight from the Africans in America study. Issue 1 (13th January 2020) - Briker, Sara M; Hormenu, Thomas; DuBose, Christopher W; Mabundo, Lilian S; Chung, Stephanie T; Ha, Joon; Sherman, Arthur; Tulloch-Reid, Marshall K; Bergman, Michael; Sumner, Anne E
Abstract : Introduction: Risk of insulin resistance, dyslipidemia, diabetes and cardiac death is increased in Asians and Europeans with normal glucose tolerance (NGT) and 1-hour glucose ≥8.6 mmol/L. As African descent populations often have insulin resistance but a normal lipid profile, the implications for Africans with NGT and glucose ≥8.6 mmol/L (NGT-1-hour-high) are unknown. Objective: We performed oral glucose tolerance tests (OGTTs) in 434 African born-blacks living in Washington, DC (male: 66%, age 38±10 years (mean±SD)) and determined in the NGT group if either glucometabolic or lipid profiles varied according to a 1-hour-glucose threshold of 8.6 mmol/L. Methods: Glucose tolerance category was defined by OGTT criteria. NGT was subdivided into NGT-1-hour-high (glucose ≥8.6 mmol/L) and NGT-1-hour-normal (glucose <8.6 mmol/L). Second OGTT were performed in 27% (119/434) of participants 10±7 days after the first. Matsuda Index and Oral Disposition Index measured insulin resistance and beta-cell function, respectively. Lipid profiles were obtained. Comparisons were by one-way analysis of variance with Bonferonni corrections for multiple comparisons. Duplicate tests were assessed by к-statistic. Results: One-hour-glucose ≥8.6 mmol/L occurred in 17% (47/272) with NGT, 72% (97/134) with pre-diabetes and in 96% (27/28) with diabetes. Both insulin resistance and beta-cell function were worse in NGT-1-hour-high than in NGT-1-hour-normal. Dyslipidemia occurred in both the diabetes and pre-diabetes groups but not in either NGT group. One-hour glucose concentration ≥8.6 mmol/L showed substantial agreement for the two OGTTs (к=0.628). Conclusions: Although dyslipidemia did not occur in either NGT group, insulin resistance and beta-cell compromise were worse in NGT-1 hour-high. Subdividing the NGT group at a 1-hour glucose threshold of 8.6 mmol/L may stratify risk for diabetes in Africans.